Development and application of the 3000 m-level multiparameter CPTu in-situ integrated test system. Issue 4 (3rd April 2023) - Yuxue, Cui; Lei, Guo; Tao, Liu; Zhongnian, Yang; Xianzhang, Ling; Xiuqing, Yang; Kai, Lu; Gang, Xue
Abstract: Accurate knowledge of the mechanical properties of deep-sea sediments and various parameters of the seafloor environment is extremely important for deep-sea geological investigations. In this paper, a set of self-developed 3000 m-level multiparameter CPTu in-situ integrated test system is developed, which successfully solves the technical problems existing in deep-sea CPTu detection technology, hydraulic fine control penetration technology, coaxial cable and optical cable composite transmission technology, etc. A multi-functional integrated probe rod is successfully developed, which contains 3000 m-level CPTu detection technology, single rod 3 D four-way stereo resistivity measurement technology, sediment geochemical environment multiparameter puncture detection technology, and rapid detection of seafloor sediment temperature gradient technology, which can simultaneously obtain in-situ physical and mechanical properties of sediments and various geochemical indicators. It can realize the synchronous operation of static penetration of deep-sea integrated probe rod, static sampling of surface sediment and undersea camera, which breaks the limitation of single parameter and ensures the authenticity and validity of data. At present, the equipment has been successfully sea-tested in the Shenhu Sea Area of the South China Sea and obtained better data feedback, which can provide guidance and technical support for deep-sea mining, gas hydrate mining, deep-sea exploration and other operations.